Isolation and screening of Pseudomonas fluorescens isolates against Fusarium oxysporum f. sp. radicis-lycopersici and their effects on seedling growth of Paraserianthes falcataria - YUSRAN YUSRAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Yusran Y. 2023. Isolation and screening of Pseudomonas fluorescens isolates against Fusarium oxysporum f.sp. radicis-lycopersici and their effects on seedling growth of Paraserianthes falcataria. Biodiversitas 24: 2294-2301. Pseudomonas fluorescens plays a major role in biological control of pathogens and plant growth promotion as well with various mechanisms. The aim of the present study was to determine the biochemical characteristics of several Pseudomonas spp. isolates and to screen them against root pathogenic fungus Fusarium oxysporum f.sp radicis-lycopersici (FORL) and to evaluate their effect on the growth enhancement of Paraserianthes falcataria (L.) I.C. Nielsen seedlings. About 28 Pseudomonas fluorescens isolates were isolated from the rhizosphere of several plants and identified based on their physiological and morphological characters as well as their biochemical reactions. All isolates were tested for their ability to suppress FORL growth in vitro. All isolates inhibited FORL growth with varying inhibition zones. Six P. fluorescens isolates showed highest inhibition zones, namely TMTP4, TMTP5, TMTP6, SCPA1, SCPB3 and Proradix. The results showed that eight Pseudomonas isolates, namely TMTP4, TMTP5, TMTP6, SCPA1, SCPB3, SMPB3, TMTA2 and Proradix had a significantly different effect compared to the control treatment in increasing the growth of Paraserianthes seedlings. Based on our findings, it was confirmed that some P. fluorescens isolates could be used as potential bio-inoculants for controlling plant diseases caused by FORL and as a biological fertilizer to increase plant growth.